Does the Source of Mesenchymal Stem Cell Have an Effect in the Management of Osteoarthritis of the Knee? Meta-Analysis of Randomized Controlled Trials. (December 2021) - Jeyaraman, Madhan; Muthu, Sathish; Ganie, Parvez Ahmad
Study Design: Meta-analysis. Objectives: To compare the efficacy and safety of bone marrow(BM)–derived mesenchymal stem cell(MSCs) and adipose-derived(AD) MSCs in the management of osteoarthritis of knee from randomized controlled trials(RCTs) available in the literature. Materials and Methods: We conducted electronic database searche from PubMed, Embase, and Cochrane Library till May 2020 for RCTs analyzing the efficacy and safety of MSCs in management of osteoarthritis of knee. Visual Analog Score(VAS) for Pain, Western Ontario McMaster Universities Osteoarthritis Index(WOMAC), Lysholm Knee Scale(Lysholm), Whole-Organ Magnetic Resonance Imaging Score(WORMS), Knee Osteoarthritis Outcome Score(KOOS), and adverse events were the outcomes analyzed. Analysis was performed in R platform using OpenMeta[Analyst] software. Results: Nineteen studies involving 811 patients were included for analysis. None of the studies compared the source of MSCs for osteoarthritis of knee and results were obtained by pooled data analysis of both sources. At 6 months, AD-MSCs showed significantly better VAS( P <0.001, P =0.069) and WOMAC( P =0.134, P =0.441) improvement than BM-MSCs, respectively, compared to controls. At 1 year, AD-MSCs outperformed BM-MSCs compared to their control in measures like WOMAC( P =0.007, P =0.150), KOOS( P <0.001; P =0.658), and WORMS( P <0.001, P =0.041), respectively. Similarly at 24 months, AD-MSCs showed significantly better Lysholm score( P =0.037) than BM-MSCs( P =0.807) although VAS improvement was better with BM-MSCs at 24 months( P <0.001). There were no significant adverse events with either of the MSCs compared to their controls. Conclusion: Our analysis establishes the efficacy, safety, and superiority of AD-MSC transplantation, compared to BM-MSC, in the management of osteoarthritis of knee from available literature. Further RCTs are needed to evaluate them together with standardized doses.